Muskox Bone of Possible Wisconsin Age from Banks Island, Northwest Territories - Maher, William J. (ARCTIC, 1968)
During a summer 1963 study of the terrestrial vertebrate fauna, a Bernard River locality was searched for fossils. The only specimen found was the right half of a left metacarpal of Ovibos moschatus with a radiocarbon age of >34,000 yr, suggesting that muskoxen were on Banks Island at the height of the Wisconsin glaciation or earlier. Conflicting views concerning the existence of a Wisconsin refugium on this island are discussed; the evidence suggests that such did exist isolated from Beringia and from any of the northern islands. Ossement de bœuf musqué d'âge wisconsin (?) provenant de l'île de Banks, T. du N.-O., Canada. Un morceau de métacarpe d'Ovibos a été trouvé en 1963 sur l'île de Banks, T. du N.-O., Canada, près de 121º54'O. et 73º23'N. L'ossement n'était pas distinct de celui d'un Ovibos moschatus. L'auteur discute de l'existence possible d'un refuge wisconsinien sur l'île de Banks. En effet, il semble avoir existé là un refuge, isolé de la Béringia. En plus d'espèces botaniques, deux espèces de petits mammifères (lemmus sibiricus et Lepus arcticus) et, peut-être, le bœuf musqué auraient survécu dans le refuge de Banks.